A Stylistic Analysis to JoJo Moyes’s the Last Letter from Your Lover: Exploring the Adjectives - Lana R. Kamal; Lanja A. Dabbagh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The aim of the current research is to undertake linguistic stylistics principals, which investigates how meaning is created in literary language and other types of texts. The purpose is to clarify how and why the author JoJo Moyes selected some adjectives and how often in her novel The Last Letter from Your Lover. The investigation is conducted to trace Jojo Moyes’ choice of adjectives that adds to her style in writing the novel. Hence, enriches the relation of the reader with the plot and the meaning of the story in general. During this process, the novel has been read thoroughly multiple times. Based on Leech and Shorts’ (1981) model, the adjective category was investigated, where the choice of adjectives and the various types are analyzed, examined, and highlighted. At the end of the analysis, it is established that the adjectives capture an array of qualities, characteristics, and emotions within the narrative. They, as versatile linguistic tools, enhance the depth and diversity of the story, creating a multifaceted and dynamic narrative within the novel. Thus, allowing the scenes to unfold vividly, playing like a movie in the readers’ minds.